PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN SUCI BANDUNG - Novari, Eri; Suhendi, Suhendi; Ghifar, Azqi Nurhidayatul (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of service quality and location on consumer satisfaction at Rumah Suci Bandung. Service quality is an important factor in improving customer satisfaction, which includes aspects of reliability, responsiveness, assurance, empathy, and physical evidence. Meanwhile, a strategic location can provide easy access for customers, thus affecting their satisfaction level.  This study uses a quantitative method with a survey approach, where data is collected through questionnaires distributed to customers of Rumah Makan Suci Bandung. The analysis technique used is multiple linear regression analysis to find out how much the influence of service quality and location variables on consumer satisfaction.  The results of the study show that the quality of service and location have a positive and significant effect on consumer satisfaction. This indicates that the better the quality of service provided and the more strategic the location of the restaurant, the higher the level of consumer satisfaction. Therefore, Rumah Makan Suci Bandung is advised to continue to improve the quality of service and maintain the advantages of the location to maintain customer loyalty